Financial Structuring as a Pathway to Enterprise Readiness through MSMEs Financial Accounting Standards Implementation in Indonesian Microenterprises - Rahmadani, Mutia; Lubis, Fauzi Arif (Celebes Scholar pg, 2025)
The current study aims at exploring how Financial Accounting Standards of Micro, Small, and Medium Entities (SAK EMKM) may increase the effectiveness of financial management and the readiness of groundwork on institutional and digital integration among Indonesian microenterprises. The research makes use of a qualitative case study design by examining a laundry business located in Jaharun A Village, Deli Serdang Regency as the typical case of a non-use firm using no digital tools, absence of formal accounting records, or institutional connection. The search of information was conducted by conducting in-depth interviews, observation on the site, and complementary documents. Analysis of the collected data was carried out by aligning the current financial practices of the enterprise with standards of SAK EMKM. Investigations reveal that the company keeps very limited and hand-written incomes i.e. expenditure books, there is no categorization of assets, liabilities or profits, and there is also no separation between business and personal accounts. Such constraints are not only based on the lack of accounting expertise but are also strongly influenced by behavioral acceptability, resource availability and lack of institutional support. However, the findings reveal that, being implemented in doses and within a specified context, SAK EMKM may successfully restructure financial conduct and address the reinforcement of internal control, as well as development of trusting relationships with third-party stakeholders. Therefore, the SAK EMKM serves as a compliance tool, and as such, as an infrastructure link to informal and inclusion.